Hydrocarbon Generation and Seepage in an Emerging Fold-and-Thrust Belt, Cenderawasih Bay, Indonesia - Baillie, Peter William; Decker, John; Gilleran, Paul; Johnstone, Tanya; Orange, Daniel L.; Teas, Philip A. (Ikatan Ahli Geologi Indonesia, 2025)
Cenderawasih Bay, a triangular embayment located at the western end of the island of New Guinea, lies within the Eastern Indonesia region of complex and rapid neotectonics. In Cenderawasih Bay, the Yapen Fault marks the boundary between the oceanic Pacific plate and continental material of the Australia tectonic plate. A fold-and-thrust belt is developing in response to left-lateral strike-slip movements on the Yapen fault system. Geochemistry from sea bottom core samples the presence of an active petroleum system within the emerging fold-and-thrust belt.